2017
DOI: 10.1007/s11136-017-1506-8
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to the quality of life of older prisoners

Abstract: Approaches enabling older prisoner to disclose their interests, experiences, and feelings are important in prison. Special attention should be given to psychiatric and age-related symptoms of older prisoners, since they may not be noted by the prison staff, as older prisoners seem to be poorer self-advocates as compared to their younger peers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
25
3
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 44 publications
4
25
3
2
Order By: Relevance
“…The low prevalence of mental disorders in this group may be a result of the specific difficulties in older prisoners expressing their needs. According to de Smet et al who studied factors related to the quality of life in older prisoners, psychiatric symptoms seemed to be noted less often in this age group because “older prisoners seem to be poorer self-advocates” than their younger mates (29).…”
Section: Discussionmentioning
confidence: 99%
“…The low prevalence of mental disorders in this group may be a result of the specific difficulties in older prisoners expressing their needs. According to de Smet et al who studied factors related to the quality of life in older prisoners, psychiatric symptoms seemed to be noted less often in this age group because “older prisoners seem to be poorer self-advocates” than their younger mates (29).…”
Section: Discussionmentioning
confidence: 99%
“…Some individual health-related characteristics have been found to influence QOL in carceral settings. De Smet and colleagues (2017) note that higher physical and psychological QOL were related to lower suicide risk. Those in prison with ADHD (attention deficit hyperactivity disorder) have reported worse QOL than those without ADHD, particularly in the areas of emotional and social functioning (Westmoreland et al, 2010).…”
Section: Qol In the Carceral Spacementioning
confidence: 92%
“…Using the WHOQOL-BREF, Combalbert and colleagues (2019) found that the highest QOL scores related to mental health and lowest scores related to environmental QOL among men in French prisons as did Mooney et al (2002) who reported that scores were highest for physical health and lowest for the environmental domain among persons detained in Irish prisons. Also employing the WHOQOL-BREF, De Smet and colleagues (2017) reported highest scores related to the physical health, though lowest scores related to the social relationships domain among persons incarcerated in Belgium prisons. This was also found in a recent study of older men incarcerated in a U.S. state prison: highest reported QOL linked to physical health and lowest reported QOL pertained to the environment (Prost, Archuleta, & Golder, 2019).…”
Section: Qol In the Carceral Spacementioning
confidence: 99%
See 2 more Smart Citations